FORMATION OF ARCHEAN CONTINENTAL LITHOSPHERIC ROOTS: THE ROLE OF MANTLE PLUMES - Wyman D.A.; Kerrich R. (My University, 2002)
Deep lithospheric roots, commonly extending to the diamond stability field, are distinctive characteristics of Archean cratons, but their origin remains controversial. The 2.7 Ga Abitibi greenstone belt initially developed in an intraoceanic setting, and provides unique insights into the formation of Archean continental lithospheric mantle. Data provided by seismic transects, young U-Pb isotopic ages in the exposed deeper crust of the Kapuskasing uplift, and anomalous Ar-Ar isotopic ages from lode gold deposits point to a late coupling of the diamondiferous Abitibi lithospheric mantle to arc crust. These constraints and a lack of Archean crust-forming events following ca. 2650 Ma indicate that the thick Abitibi cratonic root formed by the diapiric ascent of buoyant residue from which mantle plume derived komatiitic liquids had been extracted. Although substantial variation may have existed in the development of Archean cratonic roots worldwide, the evidence from the Abitibi belt indicates that all such roots were initiated with the coupling of plume-melt residue to greenstone-belt crust.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей